Bauran Pemasaran Lulur di UD. Sekar Jagat Denpasar - ANAK AGUNG MADE MULYADI PUTRA; NYOMAN PARINING; I DEWA AYU SRI YUDARI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Marketing Mix Scrub in UD. Sekar Jagat Denpasar Scrub is a type of traditional cosmetics are made from materials crumb fruits and spices that are beneficial to maintain the beauty and smoothness. The materials that can be used as a scrub is yam, avocado, papaya, turmeric, cloves, sandalwood, cocoa, coffee, tea leaves, carrots, fruits and other spices. One company that manufactures scrub is UD. Sekar Jagat.Study aims to determine the marketing mix at UD. Sekar Jagat which includes product, price, distribution, promotion and as well know the constraints faced by the company in implementing the marketing mix. Marketing mix variables include herbal products yam, strawberries, avocado, sandalwood, tea leaves, carrot, coffee, milk, chocolate, carrot, coconut oil, cream, papaya and coconut honey. Setting the selling price based on the retail price and wholesale price. Distribution of products using two channels namely producers to consumers and producers to small traders to consumers. There are two media promotion at Sekar Jagat product that is a direct product promotion and sales. Constraints faced by UD. Sekar Jagat is the price of raw materials depends on the nature and the harvest, the constraints on the distribution of transport media and promotional constraints no promtion online. Advice can be given that farmers collectors add to inventories of raw materials, distribution expanded into tourism sites such as souvenirs Bali. Keywords: marketing mix,cosmetics, producers,consumers.